Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! To find the value of [tex]\( k \)[/tex] such that [tex]\( x-3 \)[/tex] is a factor of the polynomial [tex]\( x^3 - kx^2 + x - 6 \)[/tex], we can use the Factor Theorem. The Factor Theorem states that [tex]\( x-3 \)[/tex] is a factor of a polynomial if and only if substituting [tex]\( x = 3 \)[/tex] into the polynomial gives zero.
Let's substitute [tex]\( x = 3 \)[/tex] into the polynomial and set it equal to zero:
[tex]\[ P(x) = x^3 - kx^2 + x - 6 \][/tex]
Substituting [tex]\( x = 3 \)[/tex]:
[tex]\[ P(3) = 3^3 - k(3^2) + 3 - 6 \][/tex]
Now, simplify it step-by-step:
1. Calculate [tex]\( 3^3 \)[/tex]:
[tex]\[ 3^3 = 27 \][/tex]
2. Calculate [tex]\( k \cdot 3^2 \)[/tex]:
[tex]\[ k \cdot 3^2 = 9k \][/tex]
3. Calculate the remaining constants ( [tex]\( 3 \)[/tex] and [tex]\( -6 \)[/tex] ):
[tex]\[ 3 - 6 = -3 \][/tex]
Now, combine these steps:
[tex]\[ 27 - 9k + 3 - 6 = 0 \][/tex]
Simplify the equation:
[tex]\[ 27 - 9k - 3 = 0 \][/tex]
[tex]\[ 24 - 9k = 0 \][/tex]
Solving for [tex]\( k \)[/tex]:
[tex]\[ 24 = 9k \][/tex]
[tex]\[ k = \frac{24}{9} \][/tex]
[tex]\[ k = \frac{8}{3} \][/tex]
Therefore, the value of [tex]\( k \)[/tex] that makes [tex]\( x-3 \)[/tex] a factor of [tex]\( x^3 - kx^2 + x - 6 \)[/tex] is:
[tex]\[ k = \frac{8}{3} \][/tex]
Let's substitute [tex]\( x = 3 \)[/tex] into the polynomial and set it equal to zero:
[tex]\[ P(x) = x^3 - kx^2 + x - 6 \][/tex]
Substituting [tex]\( x = 3 \)[/tex]:
[tex]\[ P(3) = 3^3 - k(3^2) + 3 - 6 \][/tex]
Now, simplify it step-by-step:
1. Calculate [tex]\( 3^3 \)[/tex]:
[tex]\[ 3^3 = 27 \][/tex]
2. Calculate [tex]\( k \cdot 3^2 \)[/tex]:
[tex]\[ k \cdot 3^2 = 9k \][/tex]
3. Calculate the remaining constants ( [tex]\( 3 \)[/tex] and [tex]\( -6 \)[/tex] ):
[tex]\[ 3 - 6 = -3 \][/tex]
Now, combine these steps:
[tex]\[ 27 - 9k + 3 - 6 = 0 \][/tex]
Simplify the equation:
[tex]\[ 27 - 9k - 3 = 0 \][/tex]
[tex]\[ 24 - 9k = 0 \][/tex]
Solving for [tex]\( k \)[/tex]:
[tex]\[ 24 = 9k \][/tex]
[tex]\[ k = \frac{24}{9} \][/tex]
[tex]\[ k = \frac{8}{3} \][/tex]
Therefore, the value of [tex]\( k \)[/tex] that makes [tex]\( x-3 \)[/tex] a factor of [tex]\( x^3 - kx^2 + x - 6 \)[/tex] is:
[tex]\[ k = \frac{8}{3} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.